Investigation of the photoisomerization property of donor-acceptor Stenhouse adducts on ester-modified glass. Issue 1 (1st August 2022) - Duan, Yongli; Sun, Fanxi; Gao, Ang; Zheng, Yonghao; Wang, Dongsheng
Abstract: The isomerization process of donor-acceptor Stenhouse adducts (DASAs) is closely related to its surrounded physicochemical environment, this work focuses on the promotion of ester-modified glass fiber to the isomerization process of DASAs compared with the untreated glass fiber. The ester-modified glass fiber is prepared through a two-stage method, the coating procedure is stepwise monitored through the scanning electron microscope(SEM) and the energy dispersive spectrometer(EDS). The ester functional groups on the outmost layer of glass fiber act as a catalyst, lowering the energy level of the intermediate state of DASAs and therefore promoting isomerization performance of DASAs where the time to reach cyclic dominant states shorten from 116 s to 82 s and the efficiency of cyclic-to-linear increased almost 6 folds.